Individual Heterogeneity and Price Responses in Tobacco Consumption: A Two-Commodity Analysis of Unbalanced Panel Data - Knut R. Wangen; Erik Biørn (Statistics Norway, Research Department, 2001)
The paper presents a panel data analysis of tobacco demand. The purpose is threefold: (i) to measure income, own-price, and cross-price responses for two tobacco commodities: cigarettes and handrolling tobacco, (ii) to investigate sociodemographic effects, and (iii) to utilize the potential offered by panel data to investigate unobserved heterogeneity. The latter is crucial for commodities where consumers have different tastes and where users tend to become addicted. Several linear and non-linear specifications of a two-equation system are estimated, using an unbalanced panel data set of Norwegian households over the period 1975 - 1994 and a modified Maximum Likelihood procedure. Differences between the results based on the sub-sample of smokers and on the pooled sample of smokers and non-smokers are interpreted. For both commodities we find a high degree of unobserved heterogeneity and several robust and "heory consistent" patterns with respect to price responses and demographic effects.
Keywords: C33; C34; D12; I18; 330; Tobacco. Panel data. Addiction. Cross-price response. Heterogeneity.